Adalimumab‐induced scalp psoriasis with severe alopecia. Issue 5 (22nd August 2019) - Özkur, Ezgi; Altunay, İlknur K. and Leblebici, Cem and Topkarcı, Zeynep and Erdem, Yasemin
Abstract: In recent years, with the increase usage of tumor necrosis factor (TNF) inhibitors, more side effects have revealed. The incidence of paradoxical psoriasis (psoriasis vulgaris, palmoplantar pustulosis, scalp psoriasis, or their combinations) ranges from 1 to 5%; however alopecia due to anti‐TNF‐α‐induced scalp psoriasis, rarely reported in the literature. We report a 37‐year‐old woman who developed palmoplantar pustulosis and scalp psoriasis with severe alopecia after 2 months of treatment with adalimumab for chronic plaque psoriasis. Biopsies from the palmar and scalp lesions showed psoriasiform changes. Adalimumab treatment was discontinued, and methotrexate was started (15 mg/weekly, subcutaneously) with topical adjuvant agents. A dramatic improvement was seen in both the skin and scalp with complete hair regrowth in 1 month. We conclude that, in anti‐TNF‐α‐induced scalp psoriasis, suspension of anti‐TNF‐α agent and systemic and topical treatments should be considered to avoid scarring alopecia.